Catalogue of the dry specimens in the carcinological collection of the Museu de Zoologia da Universidade de São Paulo, Brazil - Bento, Rodrigo Tadeu; Dall´occo, Paola Lupianhes; de Melo, Gustavo Augusto Schmidt (Zootaxa, 2007)
The carcinological Collection of the Museu de Zoologia da Universidade de São Paulo (MZUSP) contains more than 400,000 specimens. Among these are 67 lots of dry specimens. This material possesses great historical value, having been collected, identified and studied by eminent researchers. The dry specimens have now been restored by cleaning, dehydration, assembly and sealing. We provide a list of the dry lots, with information on the collection locality, collector and record number. The collection comprises 53 species in 5 infraorders: Brachyura (44 species), Anomura (3), Caridea (1), Palinura (1) and Astacidea (4).